2008
DOI: 10.1073/pnas.0803790105
|View full text |Cite
|
Sign up to set email alerts
|

A role for the mitochondrial deacetylase Sirt3 in regulating energy homeostasis

Abstract: Here, we demonstrate a role for the mitochondrial NAD-dependent deacetylase Sirt3 in the maintenance of basal ATP levels and as a regulator of mitochondrial electron transport. We note that Sirt3 ؊/؊ mouse embryonic fibroblasts have a reduction in basal ATP levels. Reconstitution with wild-type but not a deacetylase-deficient form of Sirt3 restored ATP levels in these cells. Furthermore in wild-type mice, the resting level of ATP correlates with organ-specific Sirt3 protein expression. Remarkably, in mice lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

56
1,070
8
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,144 publications
(1,136 citation statements)
references
References 26 publications
56
1,070
8
2
Order By: Relevance
“…However, despite a likely role for increased ROS production, it is not possible from the present study to determine whether impaired insulin secretion following SIRT3 knockdown occurred as a result of a primary defect in insulin secretion or as a consequence of increased beta cell apoptosis. The precise mechanisms governing increased ROS production in INS1 cells are unclear; however, in different tissues, SIRT3 has been reported to alter the acetylation status of a number of proteins linked to ROS production [20,23,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite a likely role for increased ROS production, it is not possible from the present study to determine whether impaired insulin secretion following SIRT3 knockdown occurred as a result of a primary defect in insulin secretion or as a consequence of increased beta cell apoptosis. The precise mechanisms governing increased ROS production in INS1 cells are unclear; however, in different tissues, SIRT3 has been reported to alter the acetylation status of a number of proteins linked to ROS production [20,23,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to amplifying IL1β and ROS signalling, SIRT3 may also influence beta cell function and mass by other mechanisms, including deacetylation of Ku70 [46] and glutamate dehydrogenase [20,47], and the regulation of ATP production [41].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperacetylation of mitochondrial proteins have been observed in SIRT3 knock-out mice (13,55). Several key enzymes involved in energy production in the mitochondria have been identified as SIRT3 substrates.…”
mentioning
confidence: 99%
“…Deacetylate isocitrate dehydrogenase 2 oxidatively decarboxylates isocitrate to ␣-ketoglutarate while converting NAD ϩ to NADH that promotes regeneration of antioxidants. Recently, Ahn et al (55) reported that SIRT3 Ϫ/Ϫ mouse embryonic fibroblasts have decreased ATP levels and abnormal activity of Complex 1 of the electron transport chain. Mice lacking SIRT3 showed reduced basal levels of ATP in the heart, kidney, and liver.…”
mentioning
confidence: 99%
“…SIRT3, 4 and 5 are mitochondrial proteins. SIRT3 positively regulates the activity of the acetyl-Coenzyme A synthetase 2, leading to the production of acetyl-coenzyme A (Hallows et al 2006;Schwer et al 2006), and deacetylates complex I of the respiratory chain involved in ATP production (Ahn et al 2008). Thus, SIRT3 regulates energetic cell homeostasis.…”
Section: Hdac Isoformsmentioning
confidence: 99%